Depressive symptoms and its associated factors in 13-year-old urban adolescents. - Bulhões, C. (2013)
The available estimates reveal that 20-50% of adolescents report depressive symptoms, being one of the most prevalent health problems in adolescence. The aim of this study was to assess the prevalence of depressive symptoms in a community sample of 13-year-old adolescents and identify associated features. Thirteen year-old adolescents attending private and public schools in Porto (n = 1,988, 52.2% females) were evaluated from October 2003 to June 2004 and completed a questionnaire including health behaviors and the Beck Depression Inventory II. A questionnaire on parents' socio-demographics and clinical characteristics was sent home. Data were analyzed separately by sex. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression. The prevalence of depressive symptoms was 18.8% in girls and 7.6% in boys (p < 0.001). Boys with a family history of depression and girls with smoking habits had a significantly increased risk of depressive symptoms (OR = 2.18, 95%CI 1.00-4.71; OR = 2.34, 95%CI 1.46-3.76). Menarche at an early age significantly increased the risk of depressive symptoms. The characteristics most strongly associated with depressive symptoms were family history of depression among boys, tobacco consumption and an early age at menarche among girls. The high prevalence of depressive symptoms early in adolescence calls for the awareness of public health professionals.